Effect of potassium nutrition and genotypes on yield attributes, yield and nutrients accumulation in barley (Hordeum vulgare) under low available soil potassium condition - SHIVAY, Y S; HONG, CHEN JIN; SHOUREN, DING (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out at the experimetnal farm of Zhejiang Agricultural University, Hangzhou, Peoples' Republic of China, during the winter season of 1998-99, to study the effect of potassium nutrition and genotypes on yield attributes, yield and nutrients accumlation in barley (Hordeum vulgare L. s.l.) under low available soil K condition. There were significant effects of potassium nutrition on yield attributes, yields and nutrient accumulation of barley genotypes with successive increase in K levels. The maximum grain yield (6.32 tonnes/ha) was recorded with the highest level of K nutrition (225 kg k2 O/ha) and it was 7.7, 19.9 and 35.9% higher over 150, 75 kg K2 O/ha and the control respectively. Cenotype '96-6 recorded the maximum values of yield attributes, yield and nutrient accumlation in grain as well as in straw, indicating that it is an efficient utilizer of nutients especially of K under low available soil K conditionand may be utilized for further barley-improvement programme.